Strengthening market linkages of farm households in developing countries - Mottaleb, Khondoker Abdul; Mohanty, Samarendu; Nelson, Andrew (Wiley, 2015)
Farm households in developing countries generally allocate a major portion of their resources to staple food production, mainly for self‐consumption. Hence, many of them are more or less delinked from the market. It is well recognized, however, that market participation is crucial for farm households to ensure a flow of cash income, leading to poverty alleviation and improved livelihoods. Thus, it is meaningful to understand what factors affect farm households' decision to sell food crops, which is important for strengthening their linkages with markets. The empirical literature on impacts of market linkages has seldom focused on the determinants of market participation. Using rice farm households in Bangladesh and applying a double‐hurdle model, this article demonstrates that the provision of general education and the development of agricultural infrastructure such as irrigation facilities can strengthen the market linkages of farm households by enhancing their marketable surplus through increased production. By contrast, rainfall beyond the optimum level, drought spells, and flood incidences can weaken market linkages by reducing their marketable surplus through decreased production. Specific policies such as investment in general education are drawn up based on the findings.